The role of innate immunity and inflammation in Parkinson´s disease. (22nd March 2021) - Öberg, Maria; Fabrik, Ivo; Fabrikova, Daniela; Zehetner, Nina; Härtlova, Anetta
Abstract: For many years, it was postulated that the brain is the organ behind the barrier with an autonomous need for its maintenance. This view has been changed by the concept that the central nervous system is sensitive to the immune processes occurring in the periphery as well as to the infiltration of peripheral immune cells. However, how the immune system might contribute to the development of neurodegenerative diseases, such as Parkinson's disease (PD), remains unclear. PD is a chronic neurodegenerative disorder that affects motor and cognitive functions. Although the precise cause of PD is unknown, studies in both mice and human suggest that alterations in the innate immunity may play a critical role in modulating PD progression. Here, we review recent advancements in our understanding of inflammation and the innate immune mechanisms in PD pathology.